"Female athlete" politic: Title IX and the naturalization of sex difference in public policy. (2nd January 2017) - Sharrow, Elizabeth A.
ABSTRACT: How did the passage of Title IX of the Education Amendments of 1972 politically define the "female athlete?" Since the mid-1970s, debates over the application of policy to athletic domains have been profoundly contentious. In this paper, I trace the policy deliberations concerning equity in athletics throughout the 1970s and explore the implications for our political understandings of what makes certain bodies "athletes" versus "female athletes" in contemporary sports and politics. I draw upon literatures from political science, sport sociology, and gender studies, and rely on archival methods to trace the process through which policymakers wed biological sex to policy implementation. I argue that Title IX unexpectedly became a central site for the construction of binary sex difference through three specific means: (1) conflict over the understandings of the role that biological sex should play in congressional debate before Title IX's passage, (2) conflict over application of sex to policy design in light of perceived capacities of women's bodies, and (3) naturalization of sex-segregated policy design which defines the relationship between sex and the physical body. The intersectional implications of Title IX's history demonstrate that policy has not yet fully ameliorated the raced, classed, and heterosexist inequities haunting institutions of American education.